Tourist panorama in the period of the health crisis with COVID-19: considerations for the state of Amazonas - Silene Alegre Ferreira, Rúbia; Lobato da Cunha, Edileuza; Carolina Lobato da Cunha, Paula (Seven Editora, 2023)
Tourism is one of the economic activities that represents in itself a form of use of something that the locals have as a natural endowment, which, if well used can promote among several factors,  heating of the local economy, strengthening of sectors to it directly and indirectly related, demonstration and diffusion of local cuisine, involvement of the populations living in the community where the tourist action is developed through services and products, as well as acting in the propagation of this wealth to the places of origin for the visiting tourist.   Despite the establishment of the health crisis, as a result of Covid-19, a depression is established in these sectors, following what has manifested itself in virtually all sectors of the economy. Thus, the present research aims to identify the impact on the receptive tourism sector in the state of  Amazonas as a result of the health crisis, of Covid-19. To respond to the objective that was proposed for the research, information was used in three specific moments: in the first, data from Observatur – Tourism Observatory of the State University of the Amazonas, to demonstrate the representativeness of tourism in the federation unit,  pointing out the levels of formal jobs in the tourism sector in the period before the Covid-19 Pandemic.  In the second action, the investigation was carried out in the database of AmazonasTur (State Tourism Company of Amazonas), to base the tourist panorama of the period in reference. In the third moment, we used data made available by the School of  Arts Sciences and Humanities of the University of São Paulo (EACH-U SP), of the Research Group on  Tourism Economics of the  University of  São Paulo, which also refer to the period of the pandemic.   The results show that in 2020 and  2021 there was a drastic reduction in the movement of tourists to the Amazon, both in the domestic and foreign spheres. On the other hand, the formal jobs held in the subsectors of local tourism also accompanied the depression experienced worldwide in the economy,  but also show that food and lodging services responded positively, when compared to others observed in the crisis period.  established.DOI: https://doi.org/10.56238/devopinterscie-168